Contenidos escolares en ciencias naturales desde el currículo oficial de Colombia - Cárdenas-Nava, Ana María; Martínez-Rivera, Carmen Alicia (Revista Científica, 2021)
This article offers an account of the school contents (types and levels of organization) that underlie the curricular orientations issued by the Colombian Ministry of Education for the Natural Sciences area. This study was carried out in the Interinstitutional Doctorate in Education. This research is based on the qualitative approach from an interpretative perspective under the study case methodology. The Curricular Guidelines (Lineamientos Curriculares), the Core Competency Standards (Estándares Básicos de Competencias), and the Basic Learning Rights (Derechos Básicos del Aprendizaje) were examined, and a semi-structured interview was performed with one co-author of each orientation. All the data were examined through content analysis supported by the Atlas.ti software. Different types of conceptual, procedural, and attitudinal school contents stand out as results, and some articulations between said contents and the organization proposals are evidenced, such as the devising of levels of complexity and articulating axes. It is concluded that the types of school contents are directly related to a disciplinary point of view (instructional-scientist level), whereas, for the organization of such contents, a pedagogical construction and a particular didactic (integrative-transformative level) is proposed.